PENINGKATAN KREATIVITAS SISWA MELALUI PENGOLAHAN LIMBAH KAIN PERCA DI SDN 01 JAMBESARI - Rustantono, Hendra; Masrirahayu, Masrirahayu; Andriyansah, Andriyansah; Khoiroh, Nahdziya Nafisatul; Cholifah, Tety Nur; Yanti, Yulia Eka; Tjiptady, Bella Cornelia (Jurnal Edukasi Pengabdian Masyarakat, 2025)
The problem of patchwork waste continues to increase along with the growth of garment and household industries. This waste is inorganic, difficult to decompose, and potentially polluting when burned. This community service program aims to improve the skills and creativity of 4th grade students at SDN 01 Jambesari by utilizing patchwork waste into useful and economic products, such as flower vases, photo frames, and hair accessories. The method used was direct practice (learning by doing) with simple tools without sewing machines, making it easy for students to follow. The results showed that students were able to produce crafts with attractive designs, aesthetic value, and environmental awareness. This activity not only reduces potential environmental pollution but also creates entrepreneurial opportunities from an early age.